Ownership concentration and corporate performance in East African community (EAC): The role of technical efficiency on foreign ownership among publicly listed companies - Jumanne, Bilali Basesa (2018)
The poor protection of minority shareholders among the publicly listed firms in partner states of East African Community (EAC) is associated with ownership concentration owing to a laxity to enforce legal and regulatory frameworks. This study integrates the agency theory and resource dependency theory to examine the role of foreign ownership when interacted with efficiency scores towards protection of minority shareholders in the publicly listed firms in East African Community. Using the balanced panel data of 58 non-financial publicly listed companies in EAC over the period of 2007-2015, the study measures corporate performance using Tobin’s Q, Return on Assets and Return on Equity. The panel unit root tests by Im-Pesaran-Shin and Fisher-ADF are performed and the results show that the data are stationary at first difference. The Pedroni cointegration tests show that variables have long-run relationships. Efficiency scores are developed using Data Envelopment Analysis technique. Moreover, this study employs the Generalized Method of Moments estimator to overcome endogenous problems for developing consistent and unbiased estimates to circumvent the likelihood of reporting spurious results. The major finding of this study is that the ownership concentration is negative and statistically significant determinant of corporate performance. This result implies that majority shareholders divert company assets at the expense of minority investors to demonstrate poor corporate performance and poor protection of minority shareholders. Also, monitoring and expropriation behaviour executed by majority shareholders demonstrates the existence of the U-Shaped, namely, the nonlinear relationship between ownership concentration and corporate performance among the listed companies in the partner states of EAC. This result suggests that, interests of all shareholders can be aligned with corporate objectives achieved at higher level of ownership concentration. Moreover, the positive and significant influence of foreign ownership and the interactive variable on corporate performance suggests that foreign ownership can promote protection of minority shareholders. Furthermore, the results show that at least a threshold of 0.66 of efficiency scores is required for foreign ownership to excite superior corporate performance deliberately for protection of minority shareholders and henceforth poverty reduction. Acknowledging the importance of minority investors for meticulous capital market developments and economic outcomes on country and company levels, results of this study recommend to the authorities to enforce the ownership structure diversity for efficacy corporate governance practices. Meanwhile, the authorities are urged to build and reinforce quality institutions in their jurisdictions for proper corporate governance practices. The importance of institutions emanates from their ability to stimulate corporate efficiencies and for enhancing spill over benefits of attracting potential FDI inflows henceforth promote growth. Moreover, the authorities are advised to weigh the adoption of minority shareholders watchdog technique from Malaysia which demonstrated success since 2000.